Role of ATP-sensitive potassium channels on hypoxic pulmonary vasoconstriction in endotoxemia - Turzo, Maurizio; Lasitschka, Felix; Weigand, Markus A.; Busch, Cornelius (Increased IL-17RA and IL-17RC in end-stage COPD and the contribution to mast cell secretion of FGF-2 and VEGF, 2018)
ATP-regulated potassium channels (KATP) regulate pulmonary vascular tone and are involved in hypoxic pulmonary vasoconstriction (HPV). In patients with inflammation like sepsis or ARDS, HPV is impaired, resulting in a ventilation-perfusion mismatch and hypoxia. Since increase of vascular KATP channel Kir6.1 has been reported in animal models of endotoxemia, we studied the expression and physiological effects of Kir6.1 in murine endotoxemic lungs. We hypothesized that inhibition of overexpressed Kir6.1 increases HPV in endotoxemia.
Gesehen am 13.04.2018